Peak oxygen uptake and metabolic equivalents explained by six-minute walk test: A prospective observational study in predicting heart failure patient readmission. (May 2022) - Amir, Muzakkir; Kabo, Peter; Mappangara, Idar; Djafar, Zaenab; Zainuddin, Andi Alfian; Warliani, Melda; Mustafa, Asni
Abstract: Background: Current statistics indicate that the overall cost of heart disease exceeds IDR 6.67 trillion per year. This growing concern has led researches on heart failure patient readmission in developing countries, and opened discussions on tactics to suppress hospital readmission rates. This study assesses the potential of VO2max and METs obtained from the 6-min walk test in predicting heart failure patient readmission. Methods: This seven-month prospective cohort study recruited patients with heart failure which then underwent the 6-min walk test before discharged. Walking distance, estimated VO2 max, and METs were calculated and recorded. Patients were then followed-up for 3 months to track readmissions under the same diagnosis during the research period. The correlation between VO2max and METs with patient readmission was assessed. Results: A total of 93 samples were included in this study. The results demonstrated that VO2max and METs correlate with incidence of heart failure readmission ≤30 days post discharge, with VO2max showing a moderate ability to predict patient readmissions with a cut-off of 14.5 mL/kgBW/minute (C = 0.750, p < 0.001), while METs showed a weak ability to predict readmissions with a cut-off of 3.8 (C = 0.743, p < 0.001). Conclusions: VO2 max and METs values acquired from 6MWT examination correlates with heart failure patient readmission ≤30 days. This knowledge can be used to prevent increased readmission rates, therefore hoping that it will be able to reduce the burden of treatment costs on heart failure patients. Highlights: Functional capacity contributes to reducing cardiovascular events and re-hospitalization of patients with heart failure. Conducting a 6-min walk test before patient discharge can help identify a patients' risk for readmission. VO2max and METs can be utilized to create a comprehensive treatment flow for heart failure patients to prevent readmission.